PENINGKATAN KESADARAN MULTIKULTURAL KONSELOR (GURU BK) - Agus Akhmadi (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
This study is a kind of awareness training application model for enhancing school counselors multicultural awareness. Awareness training model consists of two phases, such as (1) giving tasksfinishing tasks, and (2) reflection task analysis and reflection. Training model application followed by the use of strategy and supporting media like film display, bibliolearning can be done via discussions, presentations, speech, and role plays. This study exerted experimental research pretestpostest control group design. Research subjects were 30 counselors of MTs divided into experimental group and control group. Data collection used awareness multicultural scales, validities, reliabilities analyses, while the data analysis exerted descriptive technique and statistical analyses. Based on the data analyses the research results indicated, awareness training model affected multicultural awareness. By these findings, awareness training model could be applied effectively in the multicultural training because it affected significantly towards counselors multicultural awareness.